SELF ASSESSMENT (SA) EXERCISE FOR QUALITY HUMAN CAPITAL DEVELOPMENT IN BANGLADESH : THE CASE OF MARKETING DEPARTMENT, CHITTAGONG UNIVERSITY - Mohammed Solaiman; Md. Sarwar Uddin (Indonesian Management and Accounting Research, 2014)
The paper highlights SA exercise practices in the department of marketing, Chittagong University for creating skilled and productive marketing graduates using SWOT model for meeting the demand of knowledge economy, employability and capacity building. The SA exercise has conducted in the department through involvement of junior lecturer to senior professor, supporting staffs, Students and other stakeholders. Moreover, experts and peer groups were incorporated for making the process worthwhile, and internationally accepted. The SA exercise will build new departmental capacities and test new academic practices in the form of curriculum design and organization, academic infrastructure, students' support and advising, process control, faculty updated in the context of technical depth and breadth to delivery the quality academic program, departmental facilities such as seminar, library, class rooms, computer labs, office rooms, and the likes. Keywords: Self Assessment, Human capital, SWOT Model, Quality, Employability